Metode Memahami Al-Qur’an Dan Hadis Antara Tekstual Dan Kontekstual - Ritonga, Dedi Anton; Nur Azizah (Institut Muslim Cendekia, 2025)
The Qur'an and Hadith, as religious texts, serve as the primary sources of Islamic law. However, as divine revelations revealed to the Prophet Muhammad, the Qur'an does not explain itself (self-explanatory); rather, it was revealed in the Arabic language of the time and place in which it emerged. Since it was revealed within the Arab linguistic and cultural context, it inevitably intersects with the socio-cultural dynamics of Arab society at that time. Therefore, to understand the intended meaning of these texts, a comprehensive approach is required. Among the main approaches to understanding religious texts within the Islamic scholarly tradition are the textual and contextual approaches. The textual approach emphasizes the literal meaning of the text, referring to the structure of the language, vocabulary, and grammatical rules as found in primary sources such as the Qur'an and Hadith. In contrast, the contextual approach seeks to understand the texts through their historical, cultural, and social backgrounds at the time of revelation, while also considering contemporary societal conditions. In the formulation of Islamic law, integrating these two approaches is essential to produce an understanding that is not only normatively authentic but also practically relevant. This article explores how the integration of these two approaches can enrich the interpretation of the Qur'an and Hadith in addressing the evolving dynamics of Islamic law.